Microwave Absorption Properties of Silver Doped MWCNT Buckypaper - Tsao1, Che-Wei; Saravanan3, L.; Liu1, Jih-Hsin; Miao1, Hsin-Yuan; Wang2, Li-Chih; Pan4, Jui-Wen (Asian Journal of Chemistry, 2013)
Microwave absorbing property of composites containing Ag nanoparticles filled multiwalled carbon nanotube buckypaper (Ag-BP) has been investigated. Buckypaper doped with silver was prepared by direct dispersion and filtration method. From the low temperature resistivity measurement it was found that increasing doping level decreases the electrical conductivity of the buckypaper. 30 wt. % and 40 wt. % of Ag-BP samples shows the maximum transmission coefficient, with very high conductivity. The results demonstrate that microwave absorption of Ag-BP was attributed only due to the dielectric loss rather than other losses.The absorption peak frequency of the Ag/MWCNTs BP can be controlled easily in the presence of Ag nanoparticles into the CNT mats.